PENGGUNAAN APLIKASI EDMODO DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Kusmana, Maman; Al Hamdani, M. Djaswidi; Hayatunnufus, Alifa Baiduri (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2016)
This study aims to analyze the use of edmodo applications in improving student learning outcomes in PAI subjects. The results of this study can be summarized as follows: 1) The ability of the teacher in the preparation of the basic PAI RPP Thaharah by using the edmodo application has increased. This is evidenced by the average cycle value of 75.6 in the first cycle, reaching an average of 82.3 in the second cycle while in the third cycle an average of 91; 2) The PAI learning process in the subject of Thaharah's discussion with the use of Edmodo Application is known to increase. This can be seen from the results obtained by the teacher in the PAI learning process in the first cycle which reached an average value of 76, in the second cycle reached an average value of 84, while the third cycle reached an average of 91.3; 3) Learning outcomes of students on PAI subjects on the subject of Thaharah's discussion with the use of Edmodo Application has increased, this can be seen from the results of the learning evaluation of students. The first cycle obtained an average value of 64.4, cycle II obtained the average value of students 77.5 and cycle III obtained the average value of students 89.4.